Empowering Students’ Language Learning Strategies through Effective Teaching: Insights from Successful Nepalese English Practitioners - Sharma, Hari Maya (The Educator Journal, 2023)
English proficiency is a crucial aspect of education in Nepal, as it is in high demand in various professional fields. The development of proficiency depends on the strategies used in learning. So, this study aims to explore the learning strategies used by Nepalese English practitioners to develop their English proficiency over different time spans. The study also examines to what extent these strategies were influenced by formal teaching and teachers. The study collected English learning stories from twenty English practitioners across various parts of Nepal via email. Using the ‘analysis of narratives’ framework, also known as the ‘paradigmatic mode of analysis,’ the narratives were analysed to identify the primary learning strategies employed by the practitioners. The study found that the majority of the practitioners used imitation, recitation, and copying as their primary learning strategies. However, a few practitioners also developed their unique strategies. Formal instruction and teacher encouragement had significant influence on the learning strategies employed by nearly all of the participants. The findings suggest that formal instruction and teacher encouragement play an essential role in shaping the English language learning strategies of Nepalese English practitioners. This study has important implications for language educators as it provides insights into the learning strategies that may be effective in promoting English language proficiency among Nepalese learners.